2010
DOI: 10.1590/s1676-06032010000100030
|View full text |Cite
|
Sign up to set email alerts
|

Limb amputation by male Neotropical longhorn beetles during competition for females

Abstract: LARSON, F.K. Limb amputation by male Neotropical longhorn beetles during competition for females. Biota Neotrop. 10(1): http://www.biotaneotropica.org.br/v10n1/en/abstract?short-communication+bn02710012010. Abstract:The biology and mating behaviour of the spectacularly large and brightly coloured Neotropical longhorn beetle Schwarzerion holochlorum Bates 1872 (Coleoptera: Cerambycidae) is largely unknown. For the first time I report and photographically document violent male-male competitions for females invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…As in many different-sized cerambycid species (Hughes and Hughes 1982;Goldsmith et al 1996;Hanks et al 1998;Larsson 2010) male fighting has been reported in C. welensii, even causing amputation of legs and antennae in males engaged in violent fights (López-Pantoja et al 2008), a behaviour confirmed during our field and laboratory observations. Fights among males for the best tree may occur, as tree trunk is a mating arena as well as a food source.…”
Section: Adult Movementsupporting
confidence: 87%
See 1 more Smart Citation
“…As in many different-sized cerambycid species (Hughes and Hughes 1982;Goldsmith et al 1996;Hanks et al 1998;Larsson 2010) male fighting has been reported in C. welensii, even causing amputation of legs and antennae in males engaged in violent fights (López-Pantoja et al 2008), a behaviour confirmed during our field and laboratory observations. Fights among males for the best tree may occur, as tree trunk is a mating arena as well as a food source.…”
Section: Adult Movementsupporting
confidence: 87%
“…In contrast, male losers are expelled out, forced to find another tree and thereby become flyers. In other cerambycids, larger males are often more successful in fighting than smaller ones (Hughes and Hughes 1982;Hanks et al1998) although this size-dependent fighting advantage does not always translate into a mating advantage (Goldsmith et al 1996;Larsson 2010). Our data showed that sedentary males of C. welensii were not, however, significantly larger than flying males so that dispersal behaviour was not affected by body size as reported in Phoracantha semipunctata F. (Hanks et al 1998).…”
Section: Adult Movementsupporting
confidence: 55%
“…According to them, the male of this species uses many tactics for separating mated pairs. These violent disputes usually entail the amputation of appendices (Larsson, 2010). Ray et al (2009) noted that choice of tactic was not related by the size of challengers neither by relative size of defenders.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, la abundancia de larvas eclosionadas fue mayor en las hembras que se encontraban solas con respecto a las que tenían pareja (Tabla 1). Este comportamiento se atribuye al posible estrés ocasionado por la presencia del macho en el mismo recipiente (Larsson, 2010).…”
Section: áRboles Trampaunclassified